2009
DOI: 10.1007/s10592-009-9883-3
|View full text |Cite
|
Sign up to set email alerts
|

Population subdivision in hawksbill turtles nesting on Barbados, West Indies, determined from mitochondrial DNA control region sequences

Abstract: A new mitochondrial DNA control region survey of the Barbados hawksbill nesting population was undertaken using larger sample sizes, reanalysis of previously reported samples, and new primers that increase the fragment length sequenced. This work revealed that haplotypes originally identified as endemic to Barbados were misread sequences. Genetic variants and a geographic subdivision on a finer scale than has previously been recorded for sea turtles were identified between the Barbados leeward and windward coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
26
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 19 publications
8
26
0
1
Order By: Relevance
“…For example, many studies have grouped the Cuban fishing aggregations (Cuba A, B and D) as a single entity, perhaps because these belong to the same political jurisdiction Blumenthal et al, 2009a;Browne et al, 2010). However, this is inappropriate since these Cuban aggregations are separated by hundreds of kilometers and differ structurally, as well as in the proportion of the maturation stages present .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many studies have grouped the Cuban fishing aggregations (Cuba A, B and D) as a single entity, perhaps because these belong to the same political jurisdiction Blumenthal et al, 2009a;Browne et al, 2010). However, this is inappropriate since these Cuban aggregations are separated by hundreds of kilometers and differ structurally, as well as in the proportion of the maturation stages present .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the haplotype frequencies of Jumby Bay, Pearl Cays and Buck Island according to and Nr 1990s from both Dominican rookeries were assumed higher and similar values than the Nr 2000s respectively, based on the reported decline during these two decades. Nrs were recalculated for the Barbadian rookeries assuming that: 1) according to Browne et al (2010) the nesting on the leeward coast is 87.5% of the value informed in Beggs et al (2007), and 2) this proportion has been temporally maintained. As the Nr 1980s is not reported for Gales Point (Belize), we assumed the same value for the 1990s, and similarly the Nr 1980s and Nr 1990s of the Tobago rookery corresponded with the Nr 2000s .…”
Section: Rookeriesmentioning
confidence: 99%
“…Galápagos rookeries (GPS) apparently constitute a single individual genetic stock (the Galápagos MU; Dutton et al 2014a) that has very limited connectivity to other rookeries across the EP. Some rookeries that are separated by a distance of approximately 500 km or more are commonly considered independent genetic stocks (Dethmers et al 2006, Browne et al 2010, Dutton et al 2014a, Shamblin et al 2015. Thus the distance between MNP and GPS rookeries (ca.…”
Section: Introductionmentioning
confidence: 99%
“…Primary sex ratios vary among beaches and within clutches, as well as during the course of a nesting season, but are female-biased at almost all rookeries (Hawkes et al 2009). Whether primary sex ratios remain femalebiased in later life stages ('secondary sex ratios') is not well understood, for several reasons: (1) juvenile marine turtles and adult male turtles remain almost exclusively in the ocean, where they are difficult to survey; (2) marine turtles are highly migratory (Godley et al 2008) and thus are rarely located close to their natal area, where the primary sex ratio may be known; and (3) foraging aggregations appear to be comprised of mixed genetic stocks (Bass 1999, Diaz-Fernandez et al 1999, Bowen et al 2007, Mortimer et al 2007, Blumenthal et al 2009, Browne et al 2010. Female-biased primary sex ratios may be maintained at later life stages (Kichler et al 1999, Jensen et al 2006, Theissinger et al 2009, Hays et al 2010, Joseph & Shaw 2011, although some studies suggest that they are not (Wibbels et al 1993, Diez & Van Dam 2003.…”
Section: Temperature-dependent Sex Determinationmentioning
confidence: 99%
“…Genetic work and satellite tracking over the last 15 yr has demonstrated that hawksbill turtles sharing a Caribbean foraging site usually come from distant as well as local rookeries (Bass 1999, Diaz-Fernandez et al 1999, Horrocks et al 2001, Troëng et al 2005, Bowen et al 2007, Mortimer et al 2007, Van Dam et al 2008, Blumenthal et al 2009, Browne et al 2010, Meylan et al 2011, Moncada et al 2012. Initial haplotype data for Anegada suggests that the BVI foraging population consists of individuals from several different source rookeries throughout the Caribbean basin (Godley et al 2004), but enumerating the likely proportion of each would be an important demographic parameter for predictive models of climate change effects.…”
Section: Foraging Stock Compositionmentioning
confidence: 99%